A split luciferase-based probe for quantitative proximal determination of Gαq signalling in live cells. Issue 1 (December 2018) - Littmann, Timo; Ozawa, Takeaki; Hoffmann, Carsten; Buschauer, Armin; Bernhardt, Günther
Abstract The earlier an activation of a G protein-dependent signalling cascade at a G protein-coupled receptor (GPCR) is probed, the less amplificatory effects contribute to the measured signal. This is especially useful in case of a precise quantification of agonist efficacies, and is of paramount importance, when determining agonist bias in relation to the β-arrestin pathway. As most canonical assays with medium to high throughput rely on the quantification of second messengers, and assays affording more proximal readouts are often limited in throughput, we developed a technique with a proximal readout and sufficiently high throughput that can be used in live cells. Split luciferase complementation (SLC) was applied to assess the interaction of Gαq with its effector phospholipase C-β3. The resulting probe yielded an excellent Z' value of 0.7 and offers a broad and easy applicability to various Gαq -coupling GPCRs (hH1 R, hM1, 3, 5 R, hNTS1 R), expressed in HEK293T cells, allowing the functional characterisation of agonists and antagonists. Furthermore, the developed sensor enabled imaging of live cells by luminescence microscopy, as demonstrated for the hM3 R. The versatile SLC-based probe is broadly applicable e.g. to the screening and the pharmacological characterisation of GPCR ligands as well as to molecular imaging.